Potensi Interoperabilitas Sistem Informasi Rumah Sakit Untuk Penerapan Standar Pertukaran Data HL7 - Syauqie Muhammad Marier (Program Studi Sistem Informasi, 2018)
The use and application of Information Technology (IT) at the hospital has been widely applied. However, the interoperability, an ability to exchange patient information between the information systems, is limited. During its development in the health field, the data exchange standard of the Health Level 7 (HL7) becomes one of the most widely used approaches in the world. It is likely to be true that in this globalization era, the patient information exchange can be conducted between hospitals from different countries. Therefore, this study proposes steps to analyze the potential of the interoperability hospital information system in applying the data exchange standard of HL7 which, according to the literature review found by the researcher, almost all of the research related to data exchange in the hospital employs web service and XML methods. The steps conducted in this research include: studying the mapping between the availability of the field in the proprietary information system and the element of the messages structure of HL7; identifying and analyzing each field and element so that the potential of the mapping result can be found and the data richness of the messages structure of HL7 can be calculated; and trying out step which is conducted in one of the hospitals in Yogyakarta. The problems found during the implementation is then analyzed to obtain the results. Keywords: Potential of Interoperability, HL7, Interoperability hospital information system